Coronarin D affects TNF-α induced proliferation and osteogenic differentiation of human periodontal ligament stem cells. (December 2019) - Jiang, Chuan; Wang, Qian; Song, Miaomiao; Wang, Meng; Zhao, Li; Huang, Yong
Highlights: TNFα decreases the viability of hPDLSCs. Coronarin D improves the viability of TNFα induced hPDLSCs. Coronarin D improves the differentiation of TNF-α induced hPDLSCs. Coronarin D is involved in the anti-inflammatory effect. Abstract: Periodontitis is the most common oral disease which can destroy periodontal supporting tissue leading to tooth loss. Anti-inflammatory substances can effectively improve periodontitis. The present study was to explore whether Coronarin D could resolve the periodontal inﬂammation and improve the proliferation and osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs). After treatment with TNF-α or Coronarin D, CCK-8 assay was used to detect the viability of hPDLSCs. Alkaline phosphatase (ALP) activity kit and alizarin red staining were used to determine the ALP activity and mineralization osteogenesis ability of hPDLSCs. The cell cycle proteins (CDK2, cyclinE1, P27), differentiation-related proteins (Oct4, Sox2, Runx2) and anti-inflammatory signaling proteins (TNF-a, NF/KBp50) were detected by western blot. The results demonstrated that Coronarin D could improve the viability, proliferation, differentiation and mineralization osteogenesis of hPDLSCs induced by TNF-α. And, expression of cell cycle proteins (CDK2, cyclinE1, P27), differentiation-related proteins (Oct4, Sox2, Runx2) and anti-inflammatory signaling proteins (TNF-a, NF/KBp50) were changed after the TNF-α induced hPDLSCs treated with Coronarin D. In conclusion, the presented data indicated that Coronarin D could improve the TNF-α induced proliferation and osteogenic differentiation of human periodontal ligament stem cells.